Effective Teaching in Psychological Perspective: PAI Teacher Knowledge and Skills - Eva Latipah (Jurnal Pendidikan Agama Islam, 2021)
Effective teaching is one of psychology's greatest contributions to education. This study aims to examine effective teaching in religious learning (PAI-Islamic Education). For this purpose, this research was conducted using a library approach, namely by collecting a number of data from various sources such as scientific journals, books, and other documents related to effective teaching and learning PAI. The results of the study found that PAI teaching was effectively carried out by having the following knowledge and skills: mastery of PAI science (professional dimension); the use of attitude learning strategies, design of attitude learning plans, skills in using technology for learning aspects of attitudes, skills in assessing aspects of attitudes (pedagogic dimensions); developmentally appropriate teaching practices, teaching effectively with students from various cultural backgrounds, paying attention to individual variation, communication skills, motivating skills, classroom management skills, and commitment and motivation (psychological dimensions). The psychological dimension has the most content compared to the professional and pedagogical dimensions, which shows that effective PAI teaching should be carried out by having a certain amount of psychological knowledge and skills.